The Principle of Freedom of Contract in Property Business Agreements in Indonesia - Zaenal Mustofa; Hiro Phakin (The Eastasouth Management and Business, 2026)
The principle of freedom of contract is one of the fundamental principles in contract law that gives the parties the authority to determine the content and form of the contract according to their wishes. In the practice of property business in Indonesia, this principle plays an important role because property transactions involve high economic value and complex legal relationships. However, in reality, the application of the principle of freedom of contract is often faced with the issue of bargaining imbalance, especially between property businesses and consumers. This condition creates the potential for abuse of freedom of contract that can harm one of the parties. This study aims to examine the application of the principle of freedom of contract in property business agreements in Indonesia and to analyse the normative limitations that govern it. This study uses a normative legal research method with a legislative and conceptual approach. The results of the study indicate that the principle of freedom of contract in property business agreements in Indonesia is not absolute and must be limited by the principles of good faith, propriety, and fairness. The application of this principle in practice still tends to be formal, especially in standard agreements that limit the scope for negotiation for the weaker party. Therefore, the state and judicial institutions must play a role in ensuring that freedom of contract is applied in a balanced and fair manner and provides legal certainty for all parties involved in property business.